2021
DOI: 10.7150/jca.55727
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of CLDN6 in Hepatocellular Carcinoma Tissue and the Effects of CLDN6 on Biological Phenotypes of Hepatocellular Carcinoma Cells

Abstract: CLDN6, a member of claudin (CLDN) family, was found to be a breast cancer suppressor gene in our early experiments. However, CLDN6 was highly expressed in human hepatocellular carcinoma (hHCC) (TCGA database), and the role of CLDN6 in hHCC is still unclear. To investigate the expression of CLDN6, immunohistochemical staining was performed in hHCC tissues. As a result, hHCC tissues highly expressed CLDN6, and the expression was related to the degree of tumor's differentiation. To research the role of CLDN6 in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Notably, CLDN6 exerts carcinogenic or anti–carcinogenic effects depending on the tissue or cell type [ 27 ]. As for proliferation, CLDN6 promotes cell proliferation in human hepatocellular carcinoma, gastric cancer, and endometrial carcinoma [ 28 , 29 , 30 , 31 ]. However, we have found the proliferation of MCF–7 breast cancer cells was suppressed upon CLDN6 overexpression, but the mechanism was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CLDN6 exerts carcinogenic or anti–carcinogenic effects depending on the tissue or cell type [ 27 ]. As for proliferation, CLDN6 promotes cell proliferation in human hepatocellular carcinoma, gastric cancer, and endometrial carcinoma [ 28 , 29 , 30 , 31 ]. However, we have found the proliferation of MCF–7 breast cancer cells was suppressed upon CLDN6 overexpression, but the mechanism was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison revealed that the expression of CLDN6 in the same tumor may not be identical or even contradictory in different studies. For example, Tetsuo Ushiku et al [49] found a positive rate of 0% for CLDN6, while Yan Lu et al [50] found a positive expression rate of 79.2% in hepatocellular carcinoma. This may be related to intratumor heterogeneity, the number of cases, different experimental methods, or different manufacturers of antibodies, and further validation is needed as to whether CLDN6 can be a biomarker for identifying certain tumors.…”
Section: The Expression Of Cldn6 In Cancersmentioning
confidence: 99%
“…Studies have shown that CLDN6 inhibits the development and progression in some cancers such as breast cancer [22,24,[61][62][63], cervical cancer [56], and meningioma [64]. In hepatocellular cancer [50,65,66], gastric cancer [52,67], endometrial cancer [68,69], and ovarian cancer [70], CLDN6 has the opposite roles. The oncogenic role or conversely tumor-suppressive effect of CLDN6 in different types of cancer is shown in Table 2.…”
Section: The Malignant Phenotypes Of Cldn6 Affected In Cancersmentioning
confidence: 99%
See 2 more Smart Citations